Diskresi Pemerintah Kota Surabaya Terhadap Pelaksanaan Peraturan Pemerintah Pengganti Undang-undang Nomor 2 Tahun 2022 Tentang Cipta Kerja Untuk Percepatan Perizinan Bangunan - Wulandari, Ari (CV. Era Digital Nusantara, 2023)
This study aims to find out the explanation of discretionary policies related to the implementation of permits in the Surabaya City Government and to find out the legal consequences of discretionary policy strategies in accelerating the implementation of building permits in the City of Surabaya. The discretionary policy was carried out to overcome the stagnation of requirements for business/non-business licensing services and to streamline the administration of government in the City of Surabaya due to the enactment of the work copyright law which has changed building permits to building approvals. This aims to provide legal certainty for the government and also the community in the form of submitting business/non-business licensing services until the suitability of space utilization activities and building approvals can be issued. The writing method used in this research is normative legal research using case studies (case approach). The results of the analysis of this study indicate that the use of discretion by the Surabaya City Government regarding the implementation of Perppu Number 2 of 2022 concerning Job Creation to accelerate building permits or building approvals for building permits has an impact on two sides, namely the local government provides legal certainty in issuing certificates city plans and building approvals. Apart from that, it also provides legal certainty for the community in applying for business/non-business licensing services and vice versa increasing the local revenue of the City of Surabaya through building permit fees or building approvals.